Caracterização do consumidor de cuidados de saúde da área metropolitana de Lisboa - Simões, Nuno Filipe Rodrigues (2013)
This study aims to characterize the consumer healthcare services of the Lisbon Metropolitan Area, with the intention that it can be useful in management decisions and marketing management. Especially at a time of great changes in the field of healthcare, motivated by the economic crisis, the restructuring of the health public sector and private sector growth. The access to information is facilitated, the consumer is more informed and demanding, companies tend to be more customer-oriented, in this context; consumer knowledge is the key. A quantitative analysis is used in this study. Data collection was carried out through a questionnaire online platform. It was obtained a sample of 245 individuals residing in the Lisbon Metropolitan Area. A non-probability sample of convenience was used. We conclude that consumers of healthcare services in the Lisbon Metropolitan Area are frequent costumers, they prefer a traditional approach, following the directions of the doctor, they are sensitive to differences in healthcare facilities, and they are actively looking for information about healthcare and value added services.